A Simple Method To Purify Withanolide A From The Roots Of Withania Somnifera Dunal - S.SUMITHRADEVI,; D.PRADEEPA,; KALAISELVI SENTHIL, (International Journal of Pharma and Bio Sciences, 2011)
Withania somnifera, commonly known as Ashwagandha, is a valued herb in Ayurvedic medicine. Roots, leaves and preparations of the plant are traditionally used as tonic, hypnotic, sedative and diuretic. W.somnifera mainly contains withanolides which are specific to the Solanaceae family. Withanolides are biologically active secondary metabolites present in roots and leaves of W.somnifera. In the present study, we have standardized the protocol for the extraction and purification of Withanolide A from the dried in vivo root of W.somnifera. Withanolide A is having a high medicinal value and possesses potent anti-tumor and antioxidant properties. This study involves a detailed investigation about the accumulation of secondary metabolite content in the in vivo root both quantitatively and qualitatively extracts the pure compound using the simple techniques viz., Thin Layer Chromatography, Column Chromatography and High Pressure Liquid Chromatography.